Multi-sectoral and systemic drought risk in forested cold climates: stakeholder-informed vulnerability factors from Sweden - E. Stenfors; M. Blicharska; T. Grabs; C. Teutschbein (Hydrology and Earth System Sciences)
There is a global call for proactive drought risk management, stressing the need to further our understanding of the systemic nature of drought risk. Proactive drought risk management requires an understanding of not only the drought hazard itself, but also the underlying vulnerabilities in sociohydrological systems. As a result, drought vulnerability assessments are increasingly being conducted across the globe. However, drought vulnerability is complex and shaped by the social, ecological, and hydroclimatic context. Thus, understanding how vulnerability is manifested depending on regional, sectoral, or societal differences is crucial. Therefore, here we present an assessment of the practical relevance and relative impact of various drought vulnerability factors for water-dependent sectors and societies in forested cold climates. The analysis was based on the results of an online survey conducted in Sweden, targeting stakeholders from seven water-dependent sectors, working in authorities, private and public enterprises, NGOs, and trade associations. Respondents were asked to rate a comprehensive list of vulnerability factors, connected to sectoral and societal vulnerability as well as governance, based on their perceived impact on drought risk in their sector as well as for society as a whole. Results showed that the relevance and impact of individual vulnerability factors differed across sectors, with the forestry sector especially standing out compared to other sectors. Furthermore, the results indicate regional differences in societal vulnerability factors. The substantial list of vulnerability factors found to be relevant by the respondents demonstrates the complex nature of drought risk, as well as the importance of using caution when selecting generic vulnerability factors for applied vulnerability assessments. Furthermore, the results provide a comprehensive guide to both sectoral and societal drought vulnerability in sociohydrological systems located in forested cold climates.